Menuju Indonesia Menjadi Pusat Ekonomi Syariah Terkemuka Dunia: Sebuah Perjalanan Dynamic Governance - Djawahir, Abdillah Ubaidi (Proceedings of Annual Conference for Muslim Scholars, 2019)
Dynamic governance does not emerge spontaneously, but results from leadership efforts that have the capability to develop an advanced nation in order to be able to survive in a rapidly changing environment. This paper aims to describe the journey of dynamic governance capabilities in realizing the vision of an Independent, Prosperous and Madani Indonesia by Becoming the World's Leading Sharia Economic Center. This vision is a philosophical view and action plan for the Indonesia Islamic Economic Masterplan 2019-2024. Referring to this vision, the four main objectives are: (1) Increasing the scale of Islamic economic and financial business; (2) Increasing the ranking of the Global Islamic Economy Index; (3) Increased economic independence; and (4) Increasing the welfare index of the Indonesian people. To achieve this vision, four main strategies are used as references by stakeholders in the Islamic economy. These strategies are: (1) strengthening the halal value chain consisting of the food and beverage industry, tourism, Muslims, media, recreation, the pharmaceutical and cosmetics industry, and the renewable energy industry; (2) strengthening Islamic finance; (3) strengthening micro, small and medium enterprises (MSMEs); and (4) strengthening of the digital economy. As the four basic strategies that become the ecosystem supporting the main strategy, namely: (1) approval and governance support, (2) research and development capacity development; (3) Improving the quality and human resources; and (4) Awareness raising and public literacy.